Digital rights management for e-commerce systems - Tsolis, Dimitrios; IGI eBooks; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2009)
With the proliferation of Internet access, e-commerce systems are increasingly important as a new and effective method to distribute, transact, and exploit digital multimedia content. With the growth of multimedia content, management and protection become a critical issue, creating a need for digital rights management systems. This book highlights innovative technologies used for the design and implementation of advanced e-commerce systems facilitating digital rights management and protection. Through comprehensive coverage of the full range of technological, legal, and social issues related to digital rights management, this scholarly work provides researchers, practitioners, and students with an understanding of the most critical concerns of today's digital content industry.
Intellectual property rights -- Digital rights management: a new trend or a necessity -- Image watermarking -- Watermarking techniques for DRM applications -- Watermarking and authentication in JPEG2000 -- Securing and protecting the copyright of digital video through watermarking technologies -- Digital rights management of images and videos using robust replica detection techniques -- Digital fingerprinting based multimedia content distribution -- A digital rights management system for educational content distribution -- Digital rights management and e-commerce transactions: online rights clearance -- Digital rights management in organisations: a critical consideration with a socio-technical approach -- An advanced watermarking application for the copyright protection and management of digital images of cultural heritage case study: "Ulysses" -- Digital rights management in the cultural heritage arena: a truth or a myth -- Digital rights management: a European law perspective -- Legal issues for DRM: the future.
Includes bibliographical references (p. 350-367) and index.
Also available in print.
Mode of access: World Wide Web.
Title from PDF t.p. (viewed on May 26, 2010).
Keywords: Electronic commerce -- Technological innovations; Copyright and electronic data processing; Data protection; Computer security; Copyright protection; Digital fingerprinting; Digital rights management; E-commerce systems; Educational content distribution; Image watermarking; Intellectual property rights; Multimedia content distribution; Online rights clearance; Organizational DRM; Electronic books